Ultralight Cellulose-Derived Carbon Nanofibers from Freeze-Drying Emulsion Towards Superior Microwave Absorption - Anran Li; Zongquan Li; Lei Qian (Inorganics)
Carbon nanofibers (CNFs) are usually prepared by the carbonization of cellulose aerogels obtained from freeze-drying. However, cellulose with low concentration (below 1 wt%) is required to maintain the good porosity of the aerogels due to the strong hydrogen bonding between the cellulose molecules. In order to address this problem, here, ultralight cellulose-derived CNFs have been fabricated by freeze-drying cyclohexane (CHE)/cellulose nanofiber emulsions and carbonization. Field emission scanning electron microscopy, Raman spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy are used to characterize the resulting CNFs. It is found that the CNFs consist of three-dimensional carbon networks, whose microstructure is easily adjusted by changing the CHE ratio (from 0 to 25 vol%) in the emulsions. The CNFs with high porosity are attributed to the fact that CHE as the oil phase can effectively weaken the hydrogen bonding and reduce the aggregation of the cellulose nanofibers. Carbon lattice defects and residual oxygen-containing functional groups are regarded as polarization centers, leading to the enhancement of dielectric loss. The conductive carbon networks also improve the conductive loss. All these factors improve the microwave absorption performance of the CNFs. So, the produced CNFs exhibit a superior electromagnetic wave performance with a minimum reflection loss of −42.18 dB and effective absorption bandwidth up to 4.9 GHz at 2 mm with a filling ratio of 2 wt%. This work provides a simple, low-cost, and sustainable synthesis route for CNFs used for ultralight high-performance microwave absorption materials.